KESETARAAN PEREMPUAN BALI DALAM BERWIRASWASTADI DAERAH ALIRAN SUNGAI (DAS) UNDA KABUPATEN KLUNGKUNG - Ida Bagus Astika Pidada; I Nengah Mileh (Universitas Warmadewa, 2022)
The Unda River watershed (DAS) is located 1 kilometer in the east of Klungkung city. The Unda watershed is derived from 7 rivers, namely: Telagawaja River, Sah River, Masin River, Mangening River, Krekuk River, Barak River and Bajing River. The upper limit (north) of the Unda River is Telagawaja River including the Selat Village, Klungkung District while the downstream (south) of this river in Banjar Karangdadi and Banjar Pesurungan are in Kusamba Village, Dawan Disctrict. Due to a lot of water springs from the upper of this river, so The Unda watershed have never dried up till now. In the Unda watershed has a lot of stones and sand after the eruption of Mount Agung on February 18, 1963, the people along of this river got a lot of life. Likewise, Balinese women do not want to be left behind with men doing activities in the Unda watershed. Balinese women are known for their friendliness, faithfulness, diligent, perseverance, patience and tenacity. Based on this situation, Balinese women help make a living and other jobs. The equality of Balinese women in the Unda river with men can be seen by: excavation C, namely digging for sand and stone, shop business, money loan, religious ceremony, raising, planting flower and vegetable and washing.